2018
DOI: 10.1186/s12885-018-5171-2
|View full text |Cite
|
Sign up to set email alerts
|

An increase in the neutrophil-to-lymphocyte ratio during adjuvant chemotherapy indicates a poor prognosis in patients with stage II or III gastric cancer

Abstract: BackgroundThe neutrophil-to-lymphocyte ratio (NLR) and the platelet-to-lymphocyte ratio (PLR) are associated with poor prognoses in patients with gastric cancer; however, few studies have focused on the dynamic changes in these ratios during the treatment of patients with gastric cancer. Here, we assessed the clinical utility of changes in these ratios as prognostic indicators in patients with stage II or III gastric cancer who received adjuvant chemotherapy.MethodsWe retrospectively reviewed 100 patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 32 publications
0
22
0
4
Order By: Relevance
“…An increase in the neutrophil-to-lymphocyte ratio has been repeatedly reported to be correlated with poor prognoses including distant metastases in various types of solid cancers 8,9 . According to our data, in hosts with neutrophilia the immunosuppressive effect of neutrophils may prevail over their tumoricidal activity and lead to a net pro-tumoral effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in the neutrophil-to-lymphocyte ratio has been repeatedly reported to be correlated with poor prognoses including distant metastases in various types of solid cancers 8,9 . According to our data, in hosts with neutrophilia the immunosuppressive effect of neutrophils may prevail over their tumoricidal activity and lead to a net pro-tumoral effect.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent preclinical studies showed that exogenous G-CSF administration and other pathological conditions associated with neutrophil expansion could potentially accelerate solid tumor metastases [3][4][5][6] . In cancer patients, increased neutrophil counts (neutrophilia), and a higher neutrophil-to-lymphocyte ratio were also reported to be associated with adverse outcomes including metastatic relapse in multiple types of solid cancers such as breast cancer, gastric cancer, pancreatic cancer and melanoma [7][8][9][10][11] .…”
mentioning
confidence: 99%
“…Few studies have examined NLR in the adjuvant setting. A retrospective analysis of patients with stage II/III gastric cancer who received adjuvant chemotherapy found that an increase in NLR during adjuvant treatment was associated with a poorer prognosis (19). The precise mechanisms underlying NLR as a prognostic or predictive biomarker are unclear, but may represent a dynamic relationship between the NLR and the potential immunomodulatory effects of the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Многообразие субпопуляций иммунных клеток, а также основных продуктов их синтеза и путей совместного взаимодействия может объяснять как активацию путей противоопухолевой защиты, так и потенциирование прогрессирования заболевания. Кроме этого, анализ данных литературы последних лет показал несомненную прогностическую ценность системных воспалительных индексов, основанных на подсчете соотношений нейтрофилов, лимфоцитов и тромбоцитов в периферической крови пациентов с колоректальным раком [10], РЖ [11,12] и гепатоцеллюлярным раком [13], что позволяет использовать эти показатели в клинической практике на этапе планирования комплексного лечения пациентов со злокачественными новообразованиями, а также максимально рано выявлять признаки развития рецидива заболевания.…”
Section: экспериментальные статьиunclassified